Strengthening Gotong Royong as a Strategy to Improve Organizational Citizenship Behavior of Junior High School Teachers: A Study at the Mardi Yuana Foundation - Irianto Segu, Yosef; Kadar, Isman; Retnowati, Rita (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to explore the role of gotong royong (the value of local wisdom that emphasizes collective responsibility and mutual help) in improving the Organizational Citizenship Behavior (OCB) of teachers in the junior high school of the Mardi Yuana Foundation. Research considers it important to integrate local values in sustainable and authentic organizational behavior improvement strategies. Methods: Quantitative research with path analysis and SITOREM analysis was conducted on 138 teachers (out of a population of 210) from Yayasan Mardi Yuana junior high schools in West Java and Banten using proportional random sampling. Data were collected using a validated questionnaire (Cronbach's Alpha = 0.966) containing 35 valid question items that measured five variables: mutual cooperation (6 items), organizational culture (7 items), personality (8 items), transformational leadership (8 items), and OCB (6 items). Data analysis was conducted using SPSS with prerequisite test stages, path analysis, and SITOREM analysis. Results: Preliminary survey data showed significant challenges in teachers' OCB: 67.7% faced problems in mutual compassion (altruism), 51.5% with civic virtue, 51.5% with courtesy, and 67.7% with sportsmanship. This gap between the ideal OCB (das solen) and reality (das sein) shows the need for strategic intervention. This study identifies gotong royong as a potential strategy to overcome these gaps through strengthening authentic local values in the culture of educational organizations. Novelty: This research uniquely integrates the values of local Sundanese wisdom (the four pillars of mutual cooperation: silih asih, silih ahon, silih asuh, and silih wangi) into the framework of the universal OCB theory. This integration has not been widely explored in previous education management research. This approach based on local wisdom offers contextually and culturally relevant solutions to improve the effectiveness of educational organizations in Indonesia, with implications for the development of authentic and sustainable educational leadership